A Systematic Analysis of Two-Dimensional Face Recognition Methods - Agrawal, Arpit (International Journal of Computer Sciences and Engineering, 2025)
Face recognition is the most effective and extensively used biometric method. It's cheap, natural, and non-intrusive. Researchers have created hundreds of facial recognition methods in recent years. Based on face data processing, these methods fall into three groups. The suggested recognition system may employ the full face, particular features or parts of the face, or both global and local face characteristics. This article reviews well-known approaches in each category. First, we discuss biometric facial recognition's pros and cons. We then describe each well-known method's concept. Next, the three facial recognition methods are compared. These algorithms are applied to face recognition databases, and some results are shown. Finally, we discuss intriguing new research areas.